La casa criolla : popularmente llamada la casa chorizo - Gregorio, Roberto de, 1944- ([Buenos Aires, Argentina] : Nobuko, 2011)
Comprehensive study of popular housing in the Pampas region of Argentina. The book reviews the most popular domestic architecture, the "chorizo house," also known as "casa de patios" (house of patios), "casa estándar" (standard house) or "casa de los gringos" (house of gringos), and its incidence in the formation of the cities of the region and other parts of the country. The study used as reference the city of Rosario.
Includes statistical information.
Includes bibliographical references.
Online resource; title from PDF title page (Digitalia, viewed May 20, 2017)
Keywords: Dwellings -- Argentina -- Rosario (Santa Fe); Architecture, Domestic -- Argentina -- Rosario (Santa Fe); Urbanization -- Argentina -- Rosario (Santa Fe) -- History; Rosario (Santa Fe, Argentina) -- Buildings, structures, etc; Electronic books